Examining factors of health information communicant activeness of Chinese residents in outdoor activities during public health emergencies - Liu, Jie; Zhang, Jinhong; Hashim, Norliana; Syed Zainudin, Sharifah Sofiah (Multidisciplinary Digital Publishing Institute, 2023)
This study explores the influencing factors of residents’ outdoor health information communicant activeness under public health emergencies and analyzes the relationship between cognition, motivation, and dissemination behavior. Based on the theory of perceived risk and the Situational Theory of Problem-Solving (STOPS), this study builds a model demonstrating the factors that affect the health information communicant activeness of residents’ outdoor activities under public health emergencies and conducts empirical analysis through questionnaires and a structural equation model. Results showed that (1) perceived risk, problem recognition, and involvement recognition positively affected health information communicant activeness through situational motivation; (2) constraint recognition negatively affects health information communicant activeness through situational motivation; and (3) the referent criterion has a direct effect on communicant activeness. This study has great significance for understanding residents’ health information communicant activeness in outdoor activities and providing them with high-quality health information services.